Blue chameleon - Gravett, Emily (Simon & Schuster Books for Young Readers, 2011)
The chameleon is feeling blue because he's lonely, so he goes and visits a yellow banana, pink cockatoo, swirly snail, brown boot, and so on. Each time, not only does he change his color to match the object or animal, but he also contorts himself into a shape that matches them.